IMPLEMENTASI SISTEM INFORMASI AKUNTANSI PADA KOPERASI ANGGREK II JORONG PANDAN KECAMATAN TANJUNG RAYA KABUPATEN AGAM DIDUKUNG DENGAN MENERAPKAN APLIKASI SISTEM MULTIUSER PADA BAHASA PEMROGRAMAN JAVA DAN DATABASE MYSQL - Hari Marfalino; Guslendra Guslendra; Azlina Mega Sari (Universitas Negeri Padang, 2017)
Savings and loan activities at the cooperative is one of the routine activities. In accordance with the role of cooperatives that aim to maintain the welfare of its members. Management of bad savings and loan activities will lead to chaos in the operational activities of the cooperative. Based on the research that has been done on Cooperative Orchid II Jorong Pandan using field research methodology, library research and laboratory research, it is known that the financial data processing system is still done manually and simply. With the design of Accounting Information Systems are supported Java programming language will provide a better solution to the problems encountered. The level of error in doing the calculations can be minimized, the information produced more accurately and the data can be stored safely. Keywords: SIA, Cooperatives, Services